INTER-RELIGIOUS DIALOGUE WITHIN THE HARE KRISHNA MANDIR COMMUNITY YOGYAKARTA - Vanny Suitela (Graduate Program of Pontianak Institute of Islamic Studies, 2013)
This paper aims to know how inter-religious dialogue was grasped by Hare Krishna Mandir community in Jogjakarta. Hare Krishna Mandir is one of Hindus community boarding schools (Asram) which being in Indonesia beneath of the umbrella of International Society for Krishna Consciousness (ISKCON). Results show that core of tenet of Hare Krishna Mandir community emphasizes on the development of individual knowledge and spirituality of student as a Hindus. Somehow, the community is being aware on pluralism context of Indonesia, therefore it also gives special attention on its community relationship to the others who live surround them. The community claims the necessity to develop interreligious dialogue as basic daily approach of communication with the others. Sunday Face comprises of the embodiment of that understanding. It is a program heading on Sunday, every week, involving many participants from different backgrounds. They gather together, they talk and share some relevant issues, and they learn from one and another point of views on solution as well as contribution to those. The program obviously contributes to sustaining religious harmony in Jogjakarta, and of course it gives better understanding for Indonesian people on the importance of inter-religious dialogue in a plural society of Indonesia. In addition to, it also contributes to shape open minded, necessity to hear, to learn, and to respect one and others among not only religious people, also society at all. Key words: Hare Krishna Mandir, interreligious dialogue, Sunday Face